Video-Based CPOT Training and Its Impact on ICU Nurses’ Self-Efficacy and Pain Assessment: A Quasi-Experimental Study - Maelina Ariyanti; Heri Bahtiar; Diana Setiawati (Lembaga Bale Literasi, 2026)
Pain assessment in non-verbal critically ill patients remains a major challenge in intensive care units (ICUs). The Critical-Care Pain Observation Tool (CPOT) is recommended for identifying pain in patients who are unable to self-report; however, its successful implementation depends on nurses’ self-efficacy and performance. Video-based training may be more effective than conventional methods because it provides visual demonstrations, flexible access, and opportunities for repeated learning. Objective: This study aimed to examine the effect of video-based CPOT training on ICU nurses’ self-efficacy and pain assessment performance. A quasi-experimental crossover study was conducted among 40 ICU nurses from two hospitals in West Nusa Tenggara, Indonesia. Participants received CPOT training using both video-based and manual-book methods, separated by a two-week washout period. Self-efficacy and performance were evaluated pre- and post-intervention. Data were analyzed using paired t-test, independent t-test, Pearson correlation, and linear regression. Compared to the manual-book group, the video group demonstrated greater mean increases in self-efficacy (11.95 vs. 8.95; p < 0.001) and performance scores (43.60 vs. 38.70; p = 0.008). Furthermore, self-efficacy was positively associated with performance. In conclusion, video-based training is more effective than manual-book methods for CPOT implementation. Video- As a practical implication, integrating educational videos into routine ICU training and orientation programs can standardize pain assessment protocols, ultimately improving the quality of pain management for non-verbal critically ill patients.